2017
DOI: 10.1113/jp273933
|View full text |Cite
|
Sign up to set email alerts
|

Previous physical exercise alters the hepatic profile of oxidative‐inflammatory status and limits the secondary brain damage induced by severe traumatic brain injury in rats

Abstract: Although systemic responses have been described after traumatic brain injury (TBI), little is known regarding potential interactions between brain and peripheral organs after neuronal injury. Accordingly, we aimed to investigate whether a peripheral oxidative/inflammatory response contributes to neuronal dysfunction after TBI, as well as the prophylactic role of exercise training. Animals were submitted to fluid percussion injury after 6 weeks of swimming training. Previous exercise training increased mRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 123 publications
(224 reference statements)
1
15
0
Order By: Relevance
“…n-6 PUFAs are precursors of many proinflammatory molecules (Mika and Sledzinski, 2017). Physical exercise is known to attenuate inflammation and oxidative stress in the liver (de Castro et al, 2017). However, the inflammatory response may be triggered by many various factors, and the elevated content of n-6 PUFAs might not be enough to induce inflammation in liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…n-6 PUFAs are precursors of many proinflammatory molecules (Mika and Sledzinski, 2017). Physical exercise is known to attenuate inflammation and oxidative stress in the liver (de Castro et al, 2017). However, the inflammatory response may be triggered by many various factors, and the elevated content of n-6 PUFAs might not be enough to induce inflammation in liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This peripheric inflammation mediated by cytokines and other small molecules promotes transmigration of leukocytes and an increase in systemic inflammation and damage in peripheral organs [17], including the liver. A recent study has shown how a single fluid percussion injury (FPI) episode in the rat cortex induces significant peripheral inflammatory and oxidative stress, disrupt redox statutes, and mitochondrial function in the liver [18]. High levels of circulating cytokines elicited by brain trauma affect the response injury in the brain and contribute to a blood-brain barrier opening and neutrophil infiltration [19].…”
Section: Discussionmentioning
confidence: 99%
“…Underlying mechanism of exercise on immune cell trafficking involve changes in adhesion molecules [90] and chemokine receptor expression [91]. As a result, previous exercise reduced neutrophil infiltration to the injury side were accompanied by attenuated secondary damage in a model of severe traumatic brain injury [92].…”
Section: Modulation Of Immune Cell Traffickingmentioning
confidence: 99%